Comparison of the diagnostic value of different lymphocyte subpopulations in bronchoalveolar lavage fluid in patients with biopsy proven sarcoidosis - Tanrıverdi, Hakan; Uygur, Fırat; Örnek, Tacettin; Erboy, Fatma; Altınsoy, Bülent; Atalay, Figen; Büyükuysal, Mustafa Çağatay; Tekin, İshak Özel and Araslı, Mehmet and Tor, Müge Meltem (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Bronchoalveolar lavage is considered a helpful tool in the diagnosis of diffuse parenchimal lung diseases such as sarcoidosis. CD4/CD8 ratio is higly specific but not sensitive to distinguish sarcoidosis and other intestitial lung diseases. We aimed to compare the diagnostic value of CD4/CD8 ratio and other lmphocyte subpopulations such as CD3+16+56, CD103+, CD4+CD103+, CD8+CD103+ in bronchoalveolar lavage to distinguish sarcoidosis and other nonsarcoidosis interstitial lung diseases. Methods: Using the bronchoscopy records from 2006 to 2013, we evaluated 68 patients with biopsy proven sarcoidosis and 72 patients with clinicoradiological and/or biopsy proven diffuse parenchimal lung diseases. Cut off values, sensitivity and specificity were given for aforementioned parameters. Results: Bronchoalveolar lavage CD4/CD8 ratio, CD4+ T lymphocyte percentage, CD4+103+, CD3+CD103-, CD8+CD103+/CD103+ ratio were significantly higher in sarcoidosis than other diffuse parenchimal lung diseases whereas CD3+103+, CD3+16+56+, CD8+, CD8+CD103+, CD8+CD103+/CD8+ were significantly lower. Best cut off value of CD4/CD8 was 1.34 with sensitivity and specificity 76.4%, 79.4% respectively. The cut off values of CD4/CD8 of >3.5 and >2.5 had specificity 95.9% and 95.3%, respectively and sensitivity 52%, 41 %, respectively. Conclusion: CD4/CD8 ratio is highly specific but not sensitive for sarcoidosis diagnosis. Thus, BAL flow cytometry is not diagnostic alone without appropriate clinicoradiological and/or histopathological findings. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 305-312)